KARAKTERISTIK RUMAH TANGGA PETANI BERLAHAN SEMPIT: STRUKTUR DAN STABILITAS PENDAPATAN DI WILAYAH BERBASIS LAHAN SAWAH TADAH HUJAN (Kasus di Propinsi Jawa Tengah dan Jawa Timur) - A. ROZANY NURMANAF (SOCA: Jurnal Sosial Ekonomi Pertanian, 2003)
The aim of the study is to identify the structure and stability household income ofsmall size land holding farmers in the region where rain fed is the basic. Information abouthousehold characteristics is collected included sources of income and several factors relatedto the low-income level and instability of income. The study show that non agriculturalincome activity is the important source of household income, especially of small size landholding farmers who live in the rain fed (paddy field) area. Agricultural sector activities aredominance in the location, which has bad accessibility; but non-agricultural sector activitiesare dominance in the location with good accessibility. Level of income is higher in the lowland area with good accessibility, which supported by higher productivity of production factor.Household income in high land area is more fluctuate because most of their income camefrom seasonal activities. On the other hand, in low land area, household income morestables because most of their income came from regular income in short period of time.Thus, the application of program in the future should be oriented not only in increasinghousehold income but increasing income stability as well.